2000
DOI: 10.1379/1466-1268(2000)005<0139:hcpcfh>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

HSP72 can protect cells from heat-induced apoptosis by accelerating the inactivation of stress kinase JNK

Abstract: The major heat shock protein Hsp72 prevents heat-induced apoptosis. We have previously demonstrated that transiently expressed Hsp72 exerts its anti-apoptotic effect by suppressing the activity of stress-kinase JNK, an early component of the apoptotic pathway initiated by heat shock. On the other hand, constitutive expression of Hsp72 does not lead to suppression of heat-induced JNK activation, yet still efficiently prevents apoptosis. To address this apparent contradiction, we studied the effects of constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…HSP72 is postulated to ameliorate insulin resistance by direct inhibition of JNK (13,42) and accelerating the rate of JNK dephosphorylation (53). Consistent with this, we observed that GGA decreased the phosphorylation of JNK in high-fatfed mice.…”
Section: Discussionsupporting
confidence: 88%
“…HSP72 is postulated to ameliorate insulin resistance by direct inhibition of JNK (13,42) and accelerating the rate of JNK dephosphorylation (53). Consistent with this, we observed that GGA decreased the phosphorylation of JNK in high-fatfed mice.…”
Section: Discussionsupporting
confidence: 88%
“…Two different mechanisms may contribute to this function. Sherman and colleagues have suggested that Hsp70 reduces JNK activity by increasing the rate of its dephosphorylation (Meriin et al, 1999;Volloch et al, 2000;Gabai et al, 2000a). An alternative mechanism is suggested by studies of Park et al (2001a) who provided evidence that Hsp70 binds to JNK to prevent its phosphorylation by upstream kinases.…”
Section: How Do Hsp Protect Cells Against Oxidative Damage?mentioning
confidence: 99%
“…The extent of activation of these pathways may affect the fate of cells exposed to heat shock. Indeed, inhibition of JNK dramatically suppressed heat-induced apoptosis of lymphoid cells (11,40,58) and rat fibroblasts (60), whereas inhibition of Akt or ERK strongly increased apoptosis (35,61).…”
Section: Cell Death and Survival Pathways Activated By Heat Shockmentioning
confidence: 99%